IMPROVING STUDENTS' VOCABULARY MASTERY USING AUDIO VISUAL AIDS (AN ACTION RESEARCH AT THE FIFTH YEAR OF SD NEGERI 3 SUMBERAGUNG NGARINGAN IN 2008/2009 ACADEMIC YEAR) - Handayani, Tutik (2008)
This research aims is to describe the implementation of teaching English vocabulary using audio visual aids and the improvement result of the implementation teaching English vocabulary using audio visual aids. This research is a Classroom Action Research (CAR). The object of the study is the improving students' vocabulary mastery using audio visual aid at fifth year of SD Negeri 3 Sumberagung. The methods of collecting data of this research are: (1) observation, (2) interview, and (3) document. In analyzing the data, the writer uses an interactive model analysis that consists of three main components: (1) reducing data, (2) explaining data and (3) and drawing conclusion. The result of the research indicates that the mean of pre-test score is 5.5. In post test, the mean of score is 9.06.The result of pre-test and post test indicate that the students have a significant improvement in English vocabulary mastery. Beside that they get some interest improvement in every cycle. The students are not bored in studying English vocabulary. They looked more confidents to speak up. They also become active and full of concentration in the classroom during the lesson. The result of scores before treatment and after treatment indicates that the students have improvement in English Vocabulary mastery. Thus, it can be said that the teaching vocabulary mastery using audio visual aids is successful.